Implementasi Blended Learning System Dalam Pembelajaran Tematik di Masa Pandemi Covid 19 - Ariska Pujianti; Sukarno Sukarno; Sandra Sukmaning Adji (Jurnal Ilmiah Wahana Pendidikan, 2022)
This research was conducted at SDN 3 Gedong Wonogiri with the type of qualitative descriptive research. The data in this study are in the form of a description of the implementation of the blended learning system in thematic learning obtained through the methods of observation, interviews, and documentation. The research subjects in this study were the principal, class VI teacher, and class VI students at SDN 3 Gedong, Wonogiri. The data collected was analyzed qualitatively. Planning for the implementation of a blended learning system in thematic learning is outlined in a thematic learning implementation plan with a blended learning system with the stages of the implementation process: seeking of information, acquisition of information, and synthesizing of knowledge. Barriers to face-to-face learning are limited time, and obstacles in online learning are the problem of student cellular data quotas that run out during learning, and unstable signal networks. The solution to the obstacles to the implementation of online learning is that students who have their savings buy quotas with their savings and some students who have quotas are the responsibility of the parents. The teacher provides a solution so that students whose quotas run out to join friends who are close to where they live. Thematic learning outcomes with the blended learning system include: 1) students have an attitude of always being grateful, caring, and honest; 2) Students' skills have an average value of 3.72 with very good predicate results; and 3) learning outcomes in the aspect of student knowledge on average show a good category in each lesson content.